STUDIES ON THE INDIAN SARDINE OIL - Kamasastry, P V (Indian Journal of Fisheries, 2016)
Sardines along with other Clupeids comprise nearly 20% of the total catch which is roughly one million tons per annum. Among the sardines the oil sardines (Sardinella longiceps) form the most important group along the West Coast and the fishery spreads over October-March. During the heavy seasons the bulk of the catch is utilized for the manufacture of fish oil and fish guano. The correct assessment of the oil production is not possible as it is manufactured by the private merchants all along the coast. A rough estimate is possible from the oil sardine landings. The approximate percentage of the extractable oil from fresh sardines is 5%. The general method which has undergone very little improvement since its inception which dates back as far as forty years (1921) consists in boiling the fish with water in large iron pans over open fire and pressing the boiled mass in coir bags with the aid of vertical screw presses. The liquid is drained into settling tanks which are interconnected at top and bottom for the separation of oil and water. The separated oil is stored in tins or tanks until it is finally exported. The oil so prepared is mostly used for painting boats and for tempering steel. The versatile uses of the fish-body oils and their products have not assumed much importance in India, due to its uncertain quality and the non-availability of the good oil.